Hormone replacement therapy, renal function and heart ultrasonographic parameters in postmenopausal women: an observational study. Issue 6 (11th December 2014) - Vitolo, E.; Comassi, M.; Caputo, M. T.; Solini, A.
Summary Background and Aim A certain degree of impaired kidney function is related to an increased cardiovascular risk. The cardiovascular protection exerted in the postmenopausal state by the hormone replacement therapy (HRT) is debated. No studies have so far explored the relationship between menopause, renal function and cardiovascular risk profile in healthy menopausal women in relation with HRT. Subjects and Methods A total of 362 postmenopausal healthy women with normal albumin excretion rate were recruited and divided into two groups (HRT+ and HRT−) according to the presence or absence of HRT. All participants underwent a complete routine biochemical analyses and an echocardiogram. Results Clinical characteristics of the two groups were similar, but HRT+ showed a significantly higher estimated glomerular filtration rate (GFR; by CKD‐EPI formula). Regarding the heart ultrasonography, HRT+ had a significantly lower size of the aortic root and left atrium diameter (p = 0.038 and p = 0.012, respectively); no differences were found in the ejection fraction and Left Ventricular Mass Index (LVMI). In the whole study group, eGFR correlated inversely with LVMI and with the size of the aortic root (both p < 0.0001), being GFR the only determinant of the former by a stepwise regression. Dividing the study population according to an eGFR cut‐off (> 80 and < 80 ml/min/1.73 m2); > 80 women, in comparison with < 80, showed a significantly lower LVMI and lower size of aortic bulb, further reduced in the HRT+. Conclusion In a cohort of healthy, drug‐naïve, postmenopausal women, HRT seems to positively affect glomerular filtration and is associated with lower values of left ventricular mass and aortic root size, thus offering a further mechanism through female hormones exert cardioprotection.